Evolving imaging techniques for staging axillary lymph nodes in breast cancer. Issue 4 (April 2018) - Lowes, S.; Leaver, A.; Cox, K.; Satchithananda, K.; Cosgrove, D.; Lim, A.
Abstract : The presence and extent of axillary nodal metastases at the time of breast cancer diagnosis is a critical factor in disease prognosis and plays a central role in deciding the best treatment for patients. Accurate assessment of the axilla is therefore an essential component in staging breast cancer. Over the years, axillary staging has evolved from surgical axillary lymph node dissection (ALND), with its numerous associated long-term complications, to the much less-radical surgical sentinel lymph node excision biopsy (SLNB), the current reference standard. In parallel, radiological staging of the axilla has become increasingly more useful as our knowledge and techniques have improved. Preoperative axillary ultrasound is used widely to stage patients with breast cancer, providing an evaluation of node morphology and allowing targeted biopsy of abnormal nodes. This is important in helping stratify which patients should proceed directly to ALND and which should undergo SLNB first. Grey-scale ultrasound on its own is not perfect and can over- and underestimate axillary disease. Newer ultrasound techniques such as elastography may help to improve diagnostic confidence when visually assessing axillary nodes; for example, in more accurately assessing the extent of axillary disease burden or in differentiating benign reactive nodes from malignant nodes in equivocal cases. The use of intradermal "microbubbles" has shown great promise in being able to locate and biopsy the sentinel lymph node under ultrasound guidance, and raises the possibility that in the future such techniques may obviate the need for surgical SLNB in select patient populations.